CORRELATION ANALYSIS BETWEEN ENGLISH LANGUAGE PROFICIENCY AND EASE OF LEARNING PROGRAMMING LANGUAGE: A CASE STUDY ON STUDENTS OF THE FACULTY OF COMPUTER SCIENCE UNIVERSITY OF INTERNATIONAL BATAM - Tony Wibowo; Rosita Tandiono (Universitas Internasional Batam, 2022)
Programming capabilities in one of the most sought skills among the younger generation due to its usage among best-paid jobs in the future. Besides that, communication is also one of the highest tiers in 21st-century skills. In this study, we aim to investigate the relation between English proficiency and computer programming score among computer science undergraduate students in Batam. Data are gathered from 1438 data spanning from 2007 to 2020. Statistical analysis and Machine Learning are used to prove the relation between them results in a strong correlation between English proficiency and computer programming score.